Venous pressure measurements in vein of Galen aneurysms. - Quisling, R G; Mickle, J P (American Journal of Neuroradiology, 1989)
Venous pressures were measured within the vein of Galen aneurysm/straight sinus complex in 15 patients with Galenic arteriovenous fistulae and vein of Galen aneurysms. Pressures exceeded normal (less than 5 cm of H2O) in each instance, ranging between 9 and 55 cm of H2O. Measured values exceeding 20 cm of H2O were associated with an increased occurrence of brain calcification. Mean venous pressures were relatively higher in the patients with thalamic arteriovenous malformations, and relatively lower in patients with true vein of Galen fistulae and choroidal type malformations. A pressure gradient across the straight sinus was measured in one patient and suspected in three others when disproportionate dilatation of the vein of Galen occurred in the presence of a small or normal-sized straight sinus. No clear relationship existed between levels of venous pressure elevation and degree of ventriculomegaly. Refractory heart failure occurred only in neonates with choroidal type fistulae and no apparent venous outflow obstruction. It is likely that the degree of venous pressure elevation reflects the hemodynamic significance of arteriovenous shunt, provided it is interpreted in context with the current clinical status and the angioarchitecture of the Galenic fistula. Such data may assist in the timing of embolotherapy. Patients with lower venous pressure are not likely to develop brain calcification or seizures, and therefore can tolerate transtorcular embolotherapy staged at wider intervals.